Cambierà passo il mondo dell'istruzione? (La civiltà cattolica, 2021)
A series of interventions for the school system in Italy have been announced with a view to an ambitious reform. A bridge plan is envisaged that also includes the much-discussed “school for the summer”, but above all the National Plan for Resistance and Resilience, which includes Euro 32 billion to renew the entire education system. Life during the pandemic has presented us with some of the system’s fragilities, but these appear after all to be only the tip of the iceberg. The current education system seems to be ill-equipped when confronted with inequalities, as indicated by the data on school drop-outs, and social mobility; second, there is the issue of inadequate facilities. It is to be hoped that the recovery plan will lead to an open school, that generates connections with the world of work, but also between education and democracy.